Morphological and functional regionalization of trunk vertebrae as an adaptation for arboreal locomotion in chameleons - Julia Molnar; Akinobu Watanabe (Royal Society Open Science, 2023)
Regionalization of the vertebral column can help animals adapt to different kinds of locomotion, including arboreal locomotion. Although functional axial regionalization has been described in both chameleons and arboreal mammals, no morphological basis for this functional regionalization in chameleons has been proposed. However, recent studies have described regionalization in the presacral vertebral column of other extant squamates. To investigate possible morphological regionalization in the vertebral column of chameleons, we took morphometric measurements from the presacral vertebrae of 28 chameleon species representing all extant chameleon genera, both fully arboreal and ground-dwelling, and performed comparative analyses. Our results support chameleons exhibiting three or four presacral morphological regions that correspond closely to those in other sauropsids, but we detected evolutionary shifts in vertebral traits occurring in only arboreal chameleons. Specifically, the anterior dorsal region in arboreal chameleons has more vertically oriented zygapophyseal joints, predicting decreased mediolateral flexibility. This shift is functionally significant because stiffening of the anterior thoracic vertebral column has been proposed to help bridge gaps between supports in primates. Thus, specialization of existing morphological regions in the vertebral column of chameleons may have played an important role in the evolution of extreme arboreal locomotion, paralleling the adaptations of arboreal primates.